Verbesserung der biochemischen und biophysikalischen Surfactanteigenschaften durch transbronchiale Surfactanttherapie beim ARDS - Klein, Jennifer geb. Harodt; Justus Liebig University Giessen (My University, 2003)
Die vorliegende Studie wurde durchgeführt um den Einfluß einer transbronchialen Surfactantapplikation auf die biochemischenund biophysikalischen Eigenschaften des Surfactantsystems an Patienten mit ARDS und septischem Schock zu untersuchen. Es wurden 25 Patienten mit ARDS in die Studie eingeschlossen, die jeweils 300-500 mg/kg KG Surfactant erhielten. Es wurden zuden Zeiten 3 Stunden vor, 24 und 72 Stunden nach Surfactantapplikation eine bronchoalveoläre Lavage durchgeführt. Die Kontrollgruppe bestand aus 12 jungen lungengesunden Probanden. Es wurde das Zell-depletierte bronchoalveoläre Lavagematerial auf biochemische, immmunologische und biophysikalische Eigenschaften untersucht. Es fanden sich weitreichende Veränderungen der Surfactanteigenschaften in der BAL von ARDS-Patienten vor Surfactantapplication im Vergleich zu Lungengesunden. Diese beinhalten eine deutliche Verminderung der large surfactant aggregate und eine signifikante Verminderung des Gesamtphospholidgehaltes mit verändertem Phospholipidprofil. Es konnte bei ARDS Patienten ein deutlicher Abfall der relativen Konzentration an Phosphatidylcholin (PC) und Phosphatidylglycerol (PG) bei gleichzeitigem Anstieg von Phosphatidylinositol(PI) und Sphingomyelin (SPH) beobachtet werden. Es wurde zusätzlich ein Abfall des Palmitoylierungsgrades des PC zu Gunsten erhöhter einfacher oder mehrfach ungesättigter Fettäuren beobachtet. Die minimale Oberfflächenspannung war ebenfalls bei ARDS Patienten deutlich erhöht. Nach Surfactantapplikation stieg der Oxygenierungsquotient (PaO2/FiO2) deutlich an. Gleichzeitig wurden eine signifikante Veresserung der biochemischen Zusammensetzung der BAL mit signifikantem Anstieg des Gesamtphospholipidgehaltes und einer annähernden Normalisierung des Phospholipidprofils sowie des relativen Gehaltes an large surfactant aggregates und SP-B beobachtet. Der SP-A Gehalt innerhalb der LSA-Fraktion war weiterhin deutlich vermindert, zurückzuführen auf das fehlenden von SP-A im exogen zugeführten Surfactantpräparat.Bezüglich der biophysikalischen Aktivität konnten nur eine partielle Besserung im Hinblick auf die Oberflächenspannung nach Surfactanttherapie erziehlt werden. Eine transbronchiale Applikation größerer Mengen eines exogenen Surfactantpräparates ist somit in der Lage, eine weitreichende Besserung der Surfactanteigenschaften im alveolären Kompartiment der Patienten zu erziehlen und bewirkt paralle hierzu eine weitreichende Besserung des Gasaustausches. In wie weit durch einen solchen Ansatz die Mortalität dieser Erkrankung weiterführend gebessert werden kann, muß in nachfolgenden kontrollierten Studien verifiziert werden.

The purpose of the present study was to investigate the impact of bronchoscopic surfactant administration, on the biochemical and biophysical surfactant properties, in patients with severe and early acute respiratory distress syndrome (ARDS) and septic shock. A total number of 27 ARDS patients received 300-500 mg x kg x body x weight(-1) of a natural bovine surfactant extract (Alveofact) via a flexible bronchoscope. Bronchoalveolar lavages were performed 3 h prior to, and 15-18 h and 72 h after surfactant administration. A comparison to healthy volunteers, undergoing an identical lavage procedure, was made (control, n=12). Severe biophysical and biochemical surfactant abnormalities were encountered throughout in the ARDS patients. These included a massive alveolar protein load, a reduced percentage of large surfactant aggregates (LA), a loss of palmitoylated phosphatidylcholine species and a significant reduction of surfactant apoprotein (SP)-A, SP-B and SP-C in the LA fraction. Both minimum (gammamin) and adsorption (gammaads) surface tension values (pulsating bubble surfactometer) were dramatically increased. Surfactant treatment resulted in a marked increase in the lavagable phospholipid (PL) pool, but predominance of the alveolar surfactant-inhibitory protein load was still encountered. Far-reaching or even complete normalization of the PL profile, the LA fraction and its SP-B and SP-C (but not SP-A) content as well as the fatty acid composition of the phosphatidylcholine class was noted. Surface tension lowering properties (gammamin and gammaads) significantly improved, but were still not fully normalized. Bronchoscopic administration of large quantities of natural bovine surfactant in severe acute respiratory distress syndrome causes far-reaching restoration of biochemical surfactant properties and significant improvement, however not full normalization, of biophysical surfactant function.The purpose of the present study was to investigate the impact of bronchoscopic surfactant administration, on the biochemical and biophysical surfactant properties, in patients with severe and early acute respiratory distress syndrome (ARDS) and septic shock. A total number of 27 ARDS patients received 300-500 mg x kg x body x weight(-1) of a natural bovine surfactant extract (Alveofact) via a flexible bronchoscope. Bronchoalveolar lavages were performed 3 h prior to, and 15-18 h and 72 h after surfactant administration. A comparison to healthy volunteers, undergoing an identical lavage procedure, was made (control, n=12). Severe biophysical and biochemical surfactant abnormalities were encountered throughout in the ARDS patients. These included a massive alveolar protein load, a reduced percentage of large surfactant aggregates (LA), a loss of palmitoylated phosphatidylcholine species and a significant reduction of surfactant apoprotein (SP)-A, SP-B and SP-C in the LA fraction. Both minimum (gammamin) and adsorption (gammaads) surface tension values (pulsating bubble surfactometer) were dramatically increased. Surfactant treatment resulted in a marked increase in the lavagable phospholipid (PL) pool, but predominance of the alveolar surfactant-inhibitory protein load was still encountered. Far-reaching or even complete normalization of the PL profile, the LA fraction and its SP-B and SP-C (but not SP-A) content as well as the fatty acid composition of the phosphatidylcholine class was noted. Surface tension lowering properties (gammamin and gammaads) significantly improved, but were still not fully normalized. Bronchoscopic administration of large quantities of natural bovine surfactant in severe acute respiratory distress syndrome causes far-reaching restoration of biochemical surfactant properties and significant improvement, however not full normalization, of biophysical surfactant function.
Bronchoscopic administration of bovine natural surfactant in ARDS
Keywords: ARDS; Surfactant; BAL; Phospholipide; Poteine; ARDS; Surfactant; BAL; Bronchoscopic; ddc:610